SANOAT KORXONALARIDA INNOVATSION FAOLIYATNI BOSHQARISH XUSUSIYATLARI - Bahodirov, Shohruh (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article examines the important aspects and features of managing innovation activities in industrial enterprises. It highlights the significance of managing innovation activities, the implementation of new technologies and developments for enterprises, improving product quality, and ensuring competitiveness. The article covers various methods, strategies, and practical aspects of organizing and managing innovation processes.